Chronic Consumption of Farmed Salmon Containing Persistent Organic Pollutants Causes Insulin Resistance and Obesity in Mice - Ibrahim, Mohammad Madani; Fjære, Even; Lock, Erik-Jan; Naville, Danielle; Amlund, Heidi; Meugnier, Emmanuelle; Le Magueresse Battistoni, Brigitte; Frøyland, Livar; Madsen, Lise; Jessen, Niels; Lund, Sten; Vidal, Hubert; et al. (PLOS ONE, 2011)
Background Dietary interventions are critical in the prevention of metabolic diseases. Yet, the effects of fatty fish consumption on type 2 diabetes remain unclear. The aim of this study was to investigate whether a diet containing farmed salmon prevents or contributes to insulin resistance in mice. Methodology/Principal Findings Adult male C57BL/6J mice were fed control diet (C), a very high-fat diet without or with farmed Atlantic salmon fillet (VHF and VHF/S, respectively), and Western diet without or with farmed Atlantic salmon fillet (WD and WD/S, respectively). Other mice were fed VHF containing farmed salmon fillet with reduced concentrations of persistent organic pollutants (VHF/S-POPs). We assessed body weight gain, fat mass, insulin sensitivity, glucose tolerance, ex vivo muscle glucose uptake, performed histology and immunohistochemistry analysis, and investigated gene and protein expression. In comparison with animals fed VHF and WD, consumption of both VHF/S and WD/S exaggerated insulin resistance, visceral obesity, and glucose intolerance. In addition, the ability of insulin to stimulate Akt phosphorylation and muscle glucose uptake was impaired in mice fed farmed salmon. Relative to VHF/S-fed mice, animals fed VHF/S-POPs had less body burdens of POPs, accumulated less visceral fat, and had reduced mRNA levels of TNFα as well as macrophage infiltration in adipose tissue. VHF/S-POPs-fed mice further exhibited better insulin sensitivity and glucose tolerance than mice fed VHF/S. Conclusions/Significance Our data indicate that intake of farmed salmon fillet contributes to several metabolic disorders linked to type 2 diabetes and obesity, and suggest a role of POPs in these deleterious effects. Overall, these findings may participate to improve nutritional strategies for the prevention and therapy of insulin resistance.